UNDERSTANDING STUDENTS’ PREFERENCES OF COMMON SPACES FROM A PHYSICAL AND PSYCHOLOGICAL PERSPECTIVE - Mami Kanzaki; Mustika Wardhani (Institute of Research and Community Outreach, Petra Christian University, Indonesia, 2022)
Although common spaces in a university can serve an important role for adolescents in learning with colleagues and developing their ideas, common spaces have received insufficient research attention. Therefore, this study identified the characteristics of physical environments that promote active leaning among university students and the psychological aspects of students’ modes of being in common spaces. We conducted an online questionnaire and analyzed the data (N = 144; 86 men and 58 women; mean age = 23.5 ± 5.8 years) using cluster analysis and text-mining. We revealed three types of physical characteristics that promote students’ active learning and five groups of students’ modes of being in common spaces. The physical and psychological characteristics of the common spaces that promote active learning are discussed.